Incidences of Postpartum Depression in Adolescent Mothers: Scoping Review - Nurul Hidayah; Cesa Septiana Pratiwi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Background: Adolescent pregnancy is a pregnancy that occurs at the age of adolescents or less than 20 years. Postpartum depression is a condition of severe depression that occurs within 4-6 weeks after giving birth. Objective: To explore the scientific evidence of obstetrics related to the incidence of postpartum depression in adolescent mothers. Design: scoping review using the PRISMA-ScR checklist Method: The authors use the Arksey and O’Malley framework. The article search used three databases namely PubMed, Proquest, and Science Direct covering from January 2012 to 2022. An assessment tool was used. Review selection and characterization were carried out using critical appraisal using the Joanna Briggs Institute (JBI) study tool. Results: Out of 809 potentially relevant articles, 7 articles were included. The research articles came from 5 different countries, and the methods were RCT, cross-sectional, and qualitative. The results are presented in three themes: the prevalence of postpartum depression in adolescent mothers, risk factors for postpartum depression in adolescent mothers, and the implementation of health services and obstacles in dealing with postpartum depression in adolescent mothers. Conclusion: Based on 7 articles reviewed, it was found that 32% of adolescent mothers have the possibility of postpartum depression that requires immediate action on early assessment, detection, and intervention. Factors that contribute to the development of postpartum depression in adolescent mothers include high social support, marital problems, pressure from parents, and economic problems. Continuing midwifery care, appropriate strategies, and preventive measures including regular screening for adolescent mothers and mental service providers are needed to reduce the risk of postpartum depression in adolescent mothers. Abstrak: Latar Belakang: Kehamilan remaja merupakan kehamilan yang terjadi pada usia remaja kurang dari 20 tahun. Depresi postpartumadalah suatu kondisi depresi berat yang terjadi dalam 4-6 minggu setelah melahirkan. Tujuan: Menggali bukti ilmiah kebidanan terkait kejadian depresi postpartum pada ibu remaja. Desain: scoping review menggunakan ceklist PRISMA-ScR Metode: Penulis menggunakan kerangka Arksey dan O’Malley. Pencarian artikel menggunakan tiga databased PubMed, Proquest, Science Direct yang mencakup dari Januari 2012 sampai 2022. Alat penilaian digunakan. Seleksi review dan karakterisasi dilakukan dengan penilaian critical appraisal menggunakan studi Joanna Briggs Institude (JBI) tool. Hasil: Dari 809 artikel yang berpotensi relevan, 7 artikel dimasukan. Artikel penelitian tersebut berasal dari 5 Negara yang berbeda, dan metode RCT, Cross sectional dan kualitatif. Hasilnya disajikan dalam tiga tema : Prevalensi depresi postpartum pada ibu remaja, faktor resiko depresi postpartum pada ibu remaja dan pelaksanaan layanan kesehatan dan hambatan dalam menangani depresi postpartum pada ibu remaja. Kesimpulan: Berdasarkan 7 artikel yang dilakukan review, ditemukan bahwa bahwa 32% ibu remaja memiliki kemungkinan depresi postpartum yang memerlukan tindakan segera pada penilaian awal, deteksi dan intervensi. Faktor-faktor yang berkontribusi terhadap perkembangan depresi postpartum pada ibu remaja termasuk dukungan sosial yang tinggi, masalah perkawinan, tekanan dari orang tua dan masalah ekonomi. Asuhan kebidanan berkesinambungan, strategi dan tindakan pencegahan yang tepat termasuk skrining secara berkala untuk ibu remaja dan penyedia layanan mental diperlukan untuk mengurangi resiko depresi postpartum pada ibu remaja.